KONSEP PENJUALAN VERSUS KONSEP PEMASARAN - Mohammad Kanzunnudin (STIE Pelita Nusantara Semarang, 2009)
Generally, o company’s main purpose is obtaining profit or certain gain as maximum as possible, and sustaining for furiher improving the company’s position in the market for its longterm objective. The purpose can be achieved when the company’s selling con be held os what this has been arranged and this has been planned before. Thus, this does not mean that every company’s product or service purchased by the customers, will always bring financial benefit for the company. In this area, there are several factors should be a company’s awareness.A superior competence in understanding the customers would give a company chances to set aside its customers’ satisfaction, as a company’s ability in identifying its competitor’s moves. Sfudy Day and Nedimgodi explain that firms which are able to control the market; called as morkef driven firms; are the companies which are able to balance the two orientations well,with the result a better marketing performance, compared to other componies. The coordination between functions within the company as efforts of customers and competitors information sharing, to face the more complex competition.